Pengaruh Kepemimpinan Transformasional, Iklim Organisasi, dan Kompetensi Kerja terhadap Kinerja Karyawan: Peran Mediasi Kepuasan Kerja dan Kelelahan Kerja di Bapenda Surabaya - Edi Gunawan; I. A. Brahma Ratih; Ida Bagus Cempena (Journal of Economics, Management, and Accounting, 2025)
This study develops and validates a novel dual-mediation model to explain how transformational leadership, organizational climate, and work competence influence employee performance at the Regional Revenue Agency (Bapenda) of Surabaya. Using data from 188 employees analyzed with PLS-SEM, the model distinguishes two psychological mechanisms: the motivational pathway (job satisfaction) and the strain pathway (burnout). The findings show distinct and theoretically meaningful patterns. Transformational leadership and work competence directly improve employee performance, whereas organizational climate enhances performance only indirectly through job satisfaction, indicating full mediation. Job satisfaction emerges as the dominant mechanism, demonstrating that motivation-driven processes are more decisive for shaping performance in a public-sector bureaucracy. Although transformational leadership and organizational climate significantly reduce burnout, burnout itself shows no meaningful influence on performance a counterintuitive yet theoretically relevant result that suggests a strong resilience effect among employees. The study’s primary theoretical contribution lies in contrasting and validating these two mediating pathways, providing evidence that motivational mechanisms outweigh strain-based mechanisms in explaining employee performance. Practically, the findings underscore the importance of strengthening transformational leadership, continuous competence development, and supportive organizational climates to enhance performance in public revenue agencies.